The Implementation of Storytelling Method for History Education to Develop Nationalism Attitudes of Early Childhood in Handayani Brebes Kindergarten - Putri, Nadia Ameliana; Sugiyo Pranoto, Yuli Kurniawati (BELIA: Early Childhood Education Papers, 2017)
History education is the process of inheritance of cultural values, knowledge, skills and historical struggles of a series of past events that have already occurred which organized to function as a material in the process of learning for learners to develop awareness of history so it will not fade away within the young generation as a successor for the nation which have an impact on nationalism. Establishing history education needs to be done from an early age so that children become accustomed to observe and interpret historical events to prepare for the future. Establishing history education has to be done in a proper method. The researchers used storytelling method in history education. The purposes of this study are to explain the difference in the nationalism attitudes of early childhood students at the time before and after given treatments and to know the improvement of nationalism attitudes of early childhood students after given the treatments in order to record the results. This study used quantitative research method with quasi experimental design. The data was taken using questionnaires of nationalism scale in the early childhood students which was filled by their classroom teachers. The population of this study is all students in Handayani Kindergarten, Brebes; while the sample is 22 children in class B2 which became experiment class provided with treatments by the researchers using storytelling method in history education. Analysis of validity using product moment where 3 out of 40 items of the instruments scale of nationalism attitudes are fall and the results of the calculation with cronbach’s alpha reliability obtained score as much as 0.754 > 0.06 has proven that the instruments are reliable so that it can be used as a measurement tool in this study. The results of the study are significant in which pre-test average minimum value is 91 and average maximum value is 84.68. While the average minimum value of the post-test after the treatments is 99 and the average maximum value is 109.14. The normality of the test using a trust level 0.05% paired sample t-test so the hypothesis is accepted. There is a significant increase in early childhood students’ nationalism attitudes implementation of storytelling method in history education to develop early childhood nationalism of 16.07%.